2023
DOI: 10.1021/acs.orglett.3c01253
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Mediated Scalable Synthesis of Trifluoromethylphosphines from Phosphine Chlorides and CF3Br

Abstract: Trifluoromethylphosphines represent a rare kind of phosphine with unique electronic withdrawing properties, which lead to some distinctive reactivities. The reported TFMPhos, products from nucleophilic or electrophilic trifluoromethylation of substrates, requiring one or more steps and prepared from phosphine chlorides, are very limited in structure diversity. Herein, we report a convenient and scalable (up to 100 mmol) recipe to synthesize diverse trifluoromethylphosphines via direct radical trifluoromethylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…During our study into the development of practical and economic trifluoromethylation methods with CF 3 Br, [21] we demonstrated the TFMPhos could be synthesized from CF 3 Br and phosphine chlorides directly (Scheme 6). [22] This radical trifluoromethylation was a promising strategy to transform phosphine chlorides into the P(III)−CF 3 compounds on large scale (up to 100 mmol) with zinc as a single electron reductant. A range of substituted trifluoromethyl phosphine was readily synthesized in practical yields with broad substrate scope, and the fluoroalkyl groups were also compatible (Scheme 6a).…”
Section: Synthesis Of Trifluoromethylphosphinesmentioning
confidence: 99%
“…During our study into the development of practical and economic trifluoromethylation methods with CF 3 Br, [21] we demonstrated the TFMPhos could be synthesized from CF 3 Br and phosphine chlorides directly (Scheme 6). [22] This radical trifluoromethylation was a promising strategy to transform phosphine chlorides into the P(III)−CF 3 compounds on large scale (up to 100 mmol) with zinc as a single electron reductant. A range of substituted trifluoromethyl phosphine was readily synthesized in practical yields with broad substrate scope, and the fluoroalkyl groups were also compatible (Scheme 6a).…”
Section: Synthesis Of Trifluoromethylphosphinesmentioning
confidence: 99%
“…Considering the biological and functional activities of organic compounds significantly influenced by the trifluoromethyl group, various methodologies for the preparation of trifluoromethylated organic compounds have been developed in the past decades. Notably, Langlois’ reagent (CF 3 SO 2 Na) has generally been used in the field of radical chemistry, probably due to its high stability, commercial availability, and lower-cost. Prompted by these related publications and our previous work, we envisioned that a series of trifluoromethylated pyrrolo­[1,2- a ]­indoles could be prepared from the oxidative cyclization cascade of unactivated N -alkene-linked indoles with CF 3 SO 2 Na by a photocatalytic trifluoromethyl radical relay (Scheme ). Hopefully, this paper was also highlighted by gaining insights into reaction mechanisms through DFT-based calculation and application exploration in living-cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…8 Taking advantage of the high reactivity of alkyl radical precursors such as alkyl halides, N -hydroxyphthalimide (NHPI) esters and Katritzky salts, elegant research work by Oshima, Ogawa, Larionov, Wolf, Wu, Duan, and others has demonstrated the successful validation of radical phosphination reactions with diphosphines or chlorodiphosphines as reaction counterparts. 9 In addition, recent developments in visible-light photocatalysis have also given valuable synthetic methods to directly convert white phosphorus (P 4 ), which is by far the most industrially relevant form of elemental phosphorus, into valuable organophosphorus substances (Scheme 1b). 10 Despite the advances of these protocols, drawbacks still exist because the reactions are highly dependent on the use of pre-functionalized radical precursors.…”
Section: Introductionmentioning
confidence: 99%